Aplikasi Pengaman Web - Indra Yatini; Wiwiek Nurwiyati; IKhwan Dirga Pratama (Universitas Janabadra, 2018)
Security weaknesses in the web application are often utilized by people who are not responsible for stealing data and damaging the web, which of course this will harm web owners and interfere with the convenience of web users. It takes a way to reduce the risk of attacks on web applications that have security weaknesses. One of them is by using the Web Application Firewall. The Web Application Firewall in this study was designed to secure web applications from brute force attacks, SQL Injection, XSS, Comman Execution, and Arbitrary File Upload. This research was conducted by comparing the results obtained from testing the dummy website that has been installed with the Web Application Firewall using the PHP programming language. Keywords: Arbitrary File Upload, Brute Force, Command Execution, PHP, XSS, Web Application Firewall